Question
upstudy study bank question image url

Suppose that the functions \( f \) and \( g \) are defined as follows. \[ f(x)=\frac{6}{x+2} \quad g(x)=\frac{x}{x-3} \] Find \( \frac{g}{f} \). Then, give its domain using an interval or union of intervals. Simplify your answers. \( \left(\frac{g}{f}\right)(x)=\square \) Domain of \( \frac{g}{f}: \square \)

Ask by Medina Chan. in the United States
Feb 20,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

\[ \left(\frac{g}{f}\right)(x) = \frac{x(x+2)}{6(x-3)} \] Domain of \( \frac{g}{f}: (-\infty, -2) \cup (-2, 3) \cup (3, \infty) \)

Solution

To find \( \frac{g}{f} \), we will divide the function \( g(x) \) by \( f(x) \). 1. **Write down the functions:** \[ f(x) = \frac{6}{x+2}, \quad g(x) = \frac{x}{x-3} \] 2. **Calculate \( \frac{g}{f} \):** \[ \frac{g}{f}(x) = \frac{g(x)}{f(x)} = \frac{\frac{x}{x-3}}{\frac{6}{x+2}} \] 3. **Simplify the expression:** To divide by a fraction, we multiply by its reciprocal: \[ \frac{g}{f}(x) = \frac{x}{x-3} \cdot \frac{x+2}{6} = \frac{x(x+2)}{6(x-3)} \] Thus, we have: \[ \left(\frac{g}{f}\right)(x) = \frac{x(x+2)}{6(x-3)} \] 4. **Determine the domain of \( \frac{g}{f} \):** The domain is restricted by the points where the denominator is zero. We need to find when \( f(x) \) and \( g(x) \) are undefined. - \( f(x) \) is undefined when \( x + 2 = 0 \) or \( x = -2 \). - \( g(x) \) is undefined when \( x - 3 = 0 \) or \( x = 3 \). Therefore, the function \( \frac{g}{f}(x) \) is undefined at \( x = -2 \) and \( x = 3 \). 5. **Express the domain:** The domain of \( \frac{g}{f} \) in interval notation is: \[ (-\infty, -2) \cup (-2, 3) \cup (3, \infty) \] In conclusion, we have: \[ \left(\frac{g}{f}\right)(x) = \frac{x(x+2)}{6(x-3)} \] Domain of \( \frac{g}{f}: (-\infty, -2) \cup (-2, 3) \cup (3, \infty) \)

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

To find \( \frac{g}{f} \), we calculate \[ \frac{g}{f} = \frac{g(x)}{f(x)} = \frac{\frac{x}{x-3}}{\frac{6}{x+2}}. \] This can be simplified by multiplying by the reciprocal of \( f(x) \): \[ \frac{g}{f} = \frac{x}{x-3} \cdot \frac{x+2}{6} = \frac{x(x+2)}{6(x-3)}. \] Now, the expression simplifies to: \[ \left(\frac{g}{f}\right)(x) = \frac{x(x+2)}{6(x-3)}. \] Next, to find the domain, we need to identify values of \( x \) that would make the denominator equal to zero. Thus, we solve \( 6(x-3) = 0 \), which gives \( x = 3 \). Additionally, \( f(x) \) is also undefined when \( x+2=0 \) or \( x=-2 \). Therefore, we need to exclude both \( x = 3 \) and \( x = -2 \) from the domain. The domain of \( \frac{g}{f} \) can be expressed in interval notation as: \[ \text{Domain of } \frac{g}{f}: (-\infty, -2) \cup (-2, 3) \cup (3, \infty). \]

Related Questions

Latest Pre Calculus Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy